Evaluation of Treatment of Unstable Distal Radial Fractures by External Fixator - Rokonuzzaman, SM; Hossain, Md Aslam; Hossain, Syed Zakir; Rahman, Md Asjadur; Yasmin, Sabina; Hafizullah, Kamruddoza; Hossain, Md Mobaraque; Ahmed, Nadim (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Distal radial fractures are very common in Orthopaedic practice but still there is no unanimity about its treatment. Objective: To evaluate the external fixator for the treatment of unstable distal radius fractures. Methods: This prospective observational study was carried out from January 2018 to December 2019 over a period of two years. Twenty-five consecutive patients of both sexes between the ages of 18 to 60 years with closed or open unstable distal radius fractures with or without intraarticular extension admitted in the Department of Orthopaedic Surgery, 250 Bedded General Hospital, Tangail & several private hospitals in Tangail & Dhaka city were selected. Patients with diabetes mellitus or chronic renal or hepatic disorder or extra-articular fractures or volar & dorsal shear injuries (Barton fractures) were excluded from this study. All the patients were evaluated thoroughly including distal neurovascular status and any associated injuries ruled out. Patients were operated as early as possible. But 4 cases were lost to follow up. Remaining 21 patients were followed up for at least 6 months and a maximum period of 12 months. Results: In this series mean age of the patient was 35.71±11.65 years and males (66.7%) were predominant than females (33.3%). In this series right side was involved in 13 patients (61.9%) and left side in 8 patients (38.1%). The mechanism of injury included road traffic accident 13 (61.9%), fall on slippery ground 7 (33.3%) and occupational accident 1 (4.8%). Six patients of this study (28.6%) had associated injury other than the local soft tissue injury. Most of the patients (66.7%) were operated on the day of admission, 2 patients (9.5%) were operated within 3 days and 5 patients (23.8%) were operated within 7 days. As per AO classification, majority (38.1%) injury was type C3 fracture followed by C1 (33.3%), C2 (14.3%), B1 (9.5%) and A3 (4.8%). According to functional outcome, satisfactory was 76.2% and according to anatomical outcome, satisfactory was 85.7%. Conclusion: According to this study finding satisfactory outcome was 76.2% (functional) and 85.7% (anatomical). J Shaheed Suhrawardy Med Coll 2021; 13(1): 20-25